Cultural Matching and the Psychotherapeutic Relationship - Patterson, Seilosa W. (Auckland University of Technology, 2003)
“Cultural matching and the psychotherapeutic relationship” challenges and explores therapists’ work with cultural otherness. Firstly, it considers the history of psychoanalysis, in terms of Freud, sexism, white blindness, white privilege and racism. Some of these critical white theories continue to oppress, marginalize and colonize the culturally different client. Therapists of Aotearoa are encouraged to culturally match the changing needs of our clientele by privileging culture within the relationship. Writings from Culbertson, Makasiale, Bowden, Seeley, Christopher, Fanon and many more are reviewed to support working with cultural differences within the psychotherapeutic relationship. Case illustrations of working with Polynesian clients are shared to highlight the needs of cultural matching in assessment, diagnosis, treatment planning, and supervision. Cultural issues within training programmes are critiqued for their contemporary monocultural approach, and challenged to consider the literature of cultural knowledge and competency written internationally and also within New Zealand.
Keywords: Cross-cultural counseling; Psychotherapist and patient; Psychotherapy; Cross-cultural studies; Psychoanalysis and culture; Cultural Diversity